Asthma control and asthma medication use among Swedish elite endurance athlete - Persson, H.; Lindberg, A.; Stenfors, N. (Canadian Respiratory Journal, 2018)
Background. Asthma is common in elite athletes. In this study, we examined the use of asthma medication and asthma control in endurance athletes in Sweden and compared the findings with those in a reference group of patients with asthma. Methods. The Asthma Control Test (ACT) and a questionnaire on asthma, respiratory symptoms, and medication use were posted to endurance athletes (n = 711) and the reference group of patients with asthma (n = 1026). Four hundred and sixty-nine athletes (66%) responded, of whom 141 (20%) reported physician-diagnosed asthma. In the reference group, 397 (39%) responded. Results. Seventy-seven percent of the athletes with asthma reported using asthma medication during the previous year; 39% used short/long-acting ß2-agonists, 31% used inhaled corticosteroids, and 31% used both daily. According to the ACT scores, 19%, 24%, and 58% of athletes with asthma had uncontrolled, partially controlled, or well-controlled asthma, respectively. After adjustment, there was no difference in ACT scores or daily use of asthma medication between the study groups. Conclusions. Many endurance athletes had uncontrolled or partially controlled asthma, and one-third used inhaled corticosteroids and long-acting ß2-agonists daily. Their adjusted ACT scores and use of asthma medication were similar to the values in the reference population.